Influence of secondary ligand on structures and topologies of lanthanide coordination polymers with 1,3,5-triazine-2,4,6-triamine hexaacetic acid - Bunlawee Yotnoi (2018)
© 2015 Taylor and Francis. A series of new lanthanide coordination polymers has been synthesized and structurally characterized; [Ln 4 (TTHA) 2 (pzac)(H 3 O) 2 (H 2 O)]·5H 2 O (Ln = Pr (1a) and Nd (1b)), [Sm 8 (TTHA) 4 (pzac) 0.5 (H 3 O)(H 2 O) 7.5 ]·4H 2 O (2), [Ln 4 (HTTHA) 2 (SO 4 )(H 2 O) 4 ]·5H 2 O (Ln = Pr (3a) and Nd (3b)), where H 6 TTHA = 1,3,5-triazine-2,4,6-triamine hexaacetic acid, and H 2 pzac = 2,5-dioxo-piperazine-1,4-diacetic acid. The compounds feature 3-D frameworks comprising the deprotonated H 6 TTHA as the primary ligand and either the in situ generated pzac 2- or sulfate as the secondary ligands. The influence of the deprotonated H 6 TTHA in directing the framework structures through preferential coordination modes and molecular conformation is described. The effect of the secondary ligands in increasing the compactness of the frameworks and in the alternation of the framework topologies based on the four-connected pts type is described.